Odpowiedzi

2010-02-05T21:03:46+01:00
A)25x²+60x+36+37=16x²+48x+36+9x²+30x+25
-18x=-12
x=⅔

b)-17+9x²+6x+1=4x+3+9x²-2x-3
4x=16
x=4

c)36x²-36x+9+29x²+219=16x²-24x+9+49x²-42x+9
30x=210
x=7
Najlepsza Odpowiedź!
2010-02-05T21:11:14+01:00
A) (5x+6) ²+37=(4x+6) ²+(3x+5) ²
2x²+60x+36+37=16x²+48x+36+9x²+30x+25
2x²+60x-16x²-48x-9x²-30x=36+25-36-37
-23x²-28x=-12

b) -17+(3x+1) ²=(4x+3)+9x²–(2x+3)
-17+9x²+6x+1=4x+3+9x²-2x-3
9x²+6x-4x-9x²+2x=3-3+17-1
4x=16 |:4
x=4

c) (6x-3) ²+29x²+219=(4x-3)²+(7x-3) ²
36x²-36x+9+29x²+219=16x²-24x+9+49x²-42x+9
36x²-36x+29x²-16x²+24x-49x²+42x=9+9-9-219
-58x²+30x=-228
2010-02-05T21:16:27+01:00
A)(5x+6) ²+37=(4x+6) ²+(3x+5) ²
"-tym bede oznaczać sobie kwadrat liczby
25x'' +60x+36+37=16x''+48x+36+9x''+30x+25
25x''+60x-16x''-9x''-48x-30x=-36-37+36+25
12x=-12 / 12
x=-1

b) -17+(3x+1) ²=(4x+3)+9x²–(2x+3)
-17+9x''+6+1=4x+3+9x''-2x-3
9x''-9x''-4x+2x=17-6+3-3
-2x=10/: (-2)
x=-5

c) (6x-3) ²+29x²+219=(4x-3)²+(7x-3) ²
36x''-36x+9+29x''+219=16x''-24x+9+49x''-42x+9
36x''-36x+29x''-16x''+24x-49x''+42x=-9-219+9+9
30x=-210 /:30
x=7